The back to basics handbook : a guide to buying and working land, raising livestock, enjoying your harvest, household skills and crafts, and more - Gehring, Abigail R. (Skyhorse Pub., 2011)
Rediscover the pleasures of a healthier, greener, and more self-sufficient lifestyle. This guide, full of practical advice, is the ultimate concise guide for voluntary simplicity in the modern age.